2015
DOI: 10.1002/uog.14706
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of third‐trimester uterine artery Doppler in the prediction of brain hemodynamic deterioration and adverse perinatal outcome in small‐for‐gestational‐age fetuses

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 39 publications
2
47
0
1
Order By: Relevance
“…Our results show the same trend and reveal the utility of early maternal predictors during pregnancy for the classification of fetuses with potential long-term complications. On the contrary, the role of UtAPI Doppler as a marker of placental hypoxia and adverse perinatal outcome is supported by several publications [24,30,31,32,33,34,35,36]. Multiple predictive models for IUGR highlight its usefulness, even in the first trimester [22,24,37,38,39,40].…”
Section: Discussionmentioning
confidence: 96%
“…Our results show the same trend and reveal the utility of early maternal predictors during pregnancy for the classification of fetuses with potential long-term complications. On the contrary, the role of UtAPI Doppler as a marker of placental hypoxia and adverse perinatal outcome is supported by several publications [24,30,31,32,33,34,35,36]. Multiple predictive models for IUGR highlight its usefulness, even in the first trimester [22,24,37,38,39,40].…”
Section: Discussionmentioning
confidence: 96%
“…and delivery 36 . EFW < 3 rd centile 37 , uterine artery Doppler 38,39 and biochemical markers such as placental growth factor 40 have also been used.…”
Section: Tablementioning
confidence: 99%
“…Abnormal UtA Doppler was recently found to be associated with poorer perinatal outcome in small for gestational age (SGA) fetuses with normal umbilical artery Doppler . Cruz‐Martinez et al found that at the time of SGA diagnosis, abnormal UtA Doppler identifies a subgroup of fetuses at risk of progression to abnormal brain Doppler findings. Moreover, a model that includes UtA measurement has been proposed to identify third trimester SGA fetuses with abnormal outcome and in need of intensive monitoring, even in the presence of normal umbilical artery Doppler and cerebroplacental ratio …”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of uterine artery (UtA) Doppler indices assessed during the third trimester of pregnancy in identifying fetuses at risk of adverse outcome is increasingly reported in literature . Several authors have indeed demonstrated that small fetuses with abnormal (≥95th centile) mean UtA pulsatility index (PI) during the third trimester are at increased risk of adverse perinatal outcome and show placental signs of underperfusion . Although evidences on the usefulness of this measurement are growing, the accuracy of UtA PI evaluation at third trimester has never been investigated.…”
Section: Introductionmentioning
confidence: 99%